The Integration of Digital Tools in EFL Grammar Instruction in Indonesia’s Digital Age: Prospects and Challenges - La Sunra, La Sunra; Amaliah, Suci; Syamsuddin, Muhammad Rifqi; Mansyur, Mansyur (Journal of Language and Literature Studies, 2025)
Digital technologies are transforming grammar instruction within English as a Foreign Language (EFL) programs. However, limited knowledge exists regarding their implementation in Indonesian higher education, where access disparities and varying levels of instructor preparedness pose significant challenges. This research endeavours to bridge that gap by examining the opportunities and obstacles associated with digital grammar teaching across three undergraduate English education curricula. Employing a sequential explanatory mixed?methods approach, the study surveyed 180 undergraduate students (S1) to gather insights on their interactions with mobile grammar applications, artificial intelligence-based grammar checkers, and online quizzes. Subsequently, semi?structured interviews were conducted with ten English faculty members to contextualize the quantitative findings. The results indicate that 72?% of students experienced increased motivation when engaging with digital tools for grammar learning, 69?% reported greater autonomy in their practice, and 65?% perceived enhancements in accuracy. Nonetheless, 31?% of students relied on instructors to interpret automated feedback, and 41?% accepted corrections uncritically, reflecting an overdependence on technological solutions. The qualitative interviews revealed that while digital tools fostered greater engagement and facilitated differentiated assignments, concerns persisted regarding feedback reliability, unequal access to devices, and the necessity for instructor oversight. These findings imply that digital tools have the potential to bolster motivation, autonomy, and precision in Indonesian EFL grammar education when thoughtfully integrated within supportive infrastructural and professional development frameworks. The study underscores the critical need for equitable access, comprehensive instructor training, and deliberate curricular integration to maximize the benefits of digital grammar instruction.